Eco-enzyme Characterization and its Application as an Ammonia-Reducing Agent in Poultry Feces - Ahmad Haikal Kadir; Muhammad Irfan Said; Anie Asriany (Journal of Global Innovations in Agricultural Sciences)
The level of air pollution due to livestock farming practices is increasingly worrying. The laying hen industry, as one of the industries with the largest population, is in the international spotlight. The production of ammonia gas (NH3) from laying hen feces is suspected of playing an important role as a contributor to greenhouse gas (GHG) emissions. The existence of NH3 is thought to be reduced by protease enzyme activity. Protease enzymes can be obtained from nature cheaply and simply and are easy to produce. One of them is by utilizing Eco-Enzyme (EE) products from fruit waste. This study aims to evaluate the character of EE from fruit waste and examine its effect in reducing NH3 gas. This study uses basic material from laying hen feces as a source of NH3 gas. The study is divided into 2 series of activities, namely (1) evaluating the character of EE from fruit waste and (2) evaluating the applied effect of EE on laying hen feces for a specific time. The study was conducted experimentally. A total of three ratios of fruit waste mixtures were used (1) 100% pineapple; (2) (pineapple + papaya) (ratio 50%:50%); (3) 100% papaya, as a source of EE and as many as four EE dilution ratios to be applied in the treatment, namely: P0 = 0% EE + 100% water (v/v)(control); P1 = 100% EE + 0% water (v/v); P2 = 90% EE + 10% water (v/v); P3 = 80% EE + 20% water (v/v). Reduction time is used 3 times, namely, M0 = 0th minute, M1 = 15th minute, and M2 = 30th minute. Data were processed statistically using a Completely Randomized Design with a Factorial pattern. Each treatment was repeated 3 times (4x3x3). Data were analyzed descriptively (enzyme character parameters) and statistically with ANOVA (NH3 gas production, temperature and humidity kinetics). The results showed that the difference in the ratio of fruit waste mixture did not show a significant effect (P>0.05) on the pH value of EE, enzyme activity, and total LAB bacteria. Implementation of P1 (100% EE + 0% water) showed the highest effectiveness in reducing ammonia gas within 15 minutes after application to feces. Keywords: Climate change, GHG emission, pollution, waste management, ammonia mitigation, bioremediation, fermentation.